Preferensi Konsumen Dan Strategi Pemasaran Terung Organik Di Kebun Praktek Fakultas Pertanian Universitas Nusa Nipa Indonesia Kecamatan Alok Kabupaten Sikka - Alwin Delastrada Owon; Yoseph Yakob Da Rato (Jurnal Ilmiah Wahana Pendidikan, 2021)
The agricultural sector is a sector that has a strategic role in the structure of the Indonesian economy. One of the potential agricultural products is vegetables which are currently widely cultivated in the form of organic vegetables. The type of research used is descriptive qualitative research, which describes relevant data to consumer preferences and formulates marketing strategies in accordance with a predetermined marketing mix. Most respondents like the taste of eggplant because it tastes good and has become a culture for daily consumption, compared to the packaging given because consumers often find packaging in the form of plastic so that it is familiar to use and it can be seen that some respondents feel that it does not need to be fixed, Most respondents like the price of eggplant vegetable products that are affordable and easy to enjoy by all groups, most respondents like the location that is easy to reach, because it is strategically located in the middle of the city and the majority of respondents think that promotions are neutral due to promotions carried out by the Faculty garden Agriculture itself is still unknown to many circles.